Struggling with the Environment: Land Use and Productivity - Thoen, Erik; Soens, Tim (Brepols, 2015)
Agriculture is always a struggle with the environment since agricultural production is in fact applied ecology. However, in the past the struggle with the environment was to a large extent determined by the social organisation which was regionally very diverse. The aim of this volume is to find out how, when and within which structural boundaries, land was made useful for agriculture. In the first part of each chapter, this is studied in general, focusing on the evolution of land use: how and why was land reclaimed and by whom? How intensively was this land used? Which actors played a part in this process? What were the environmental and social limits? In the second part the production techniques and production systems are scrutinized: crop choices, crop rotations, the importance of fallow and cattle, crop yields etc. All this is examined in light of different farming strategies and social conditions. The comparative approach of this volume in the Rural Economy and Society Series also enables a new and innovating perspective on the occurrence and impact of ‘agricultural’ and ‘green’ revolutions in the past.